The ‘Nirai’ guitar (‘Ichigo Ichie’) of Okinawa, Japan - Duin, Ezra M. A.; Hamdan, Sinin; Said, Khairul A. M.; Sinin, Aaliyawani Ezzerin; Musib, Ahmad Faudzi; Sosiati, Harini (North Carolina State University, 2025)
The ‘nirai’ instrument is a mix of ‘sanshin’ and guitar. In this study, the sound was analysed with a PicoScope oscilloscope. The ‘sanshin’ tuning is a fifth, root, and fifth. In the key of C, these notes are G, C, G (GCG). When a low C is added in ‘nirai’ it makes the tuning a root, fifth, root, fifth. The ‘nirai’ was tuned to the key of G; the 4th, 3rd, 2nd and 1st string was G2 (100 Hz), D3 (147 Hz), G3 (197 Hz), and D4 (296 Hz). String 4, 3, 2 and 1 displayed 25, 25, 19 and 12 partials frequencies, respectively. The 24th, 17th and 13th harmonics are missing in string 4, 3 and 2. The difference in numbers of partials reflect dissimilar timbre. The findings provide information on hybrid instruments. Understanding of musical aspects aspires to modern, creative and technological demands by looking at the design, construction, and cultural importance. The results contribute to creating new hybrid instruments that blend the sounds, styles and aesthetics of other musical traditions, making them more widely available. By informing educational initiatives, instrument production and performance techniques, these findings can foster innovation and cultural preservation in the world of music.